The impacts of the COVID-19 pandemic on the Brazilian service sector (Research, Society and Development, 2021)
The service sector is responsible for 74% of the Gross Domestic Product in Brazil. Given the relevance of the sector in recent years, the present study aims to analyze the impacts caused by the pandemic of the new coronavirus on the services sector in the country. The methodology used is based on the Annual Survey of Commerce, Industry and Services, as well as the Monthly Survey of Services of May 2020 released by Brazilian Micro and Small Business Support Service (SEBRAE). The results show that the service sector was the one that most grew in numbers of companies and job creation in the last years. In the first five months of the year, volume and revenue declined in all five service classifications used in the data analysis. The sharpest drop was in tourism-related activities.